Effects of dietary soybean lecithin on growth performance, hematological, biochemical, serum lipid, and immune responses in common carp (Cyprinus carpio) - Milad Adel; Mehdi Gholaghaie; Rolf Erik Olsen; Simon J. Davies; Thavasimuthu Citarasu; Brian C. Small; Caterina Faggio (Animal Feed Science and Technology, 2026)

Effects of a plantmeal vs. fishmeal diet on intestinal integrity between two strains of rainbow trout (Oncorhynchus mykiss) reveal regional, strain, and diet differences - Marina Subramaniam; Kenneth E. Overturf; Sara Schwarz; Brian C. Small (Aquaculture, 2026)

Bile acid supplementation in alternative lipid-based diets: Effects on growth, histopathology and digestibility in rainbow trout (Oncorhynchus mykiss) - Abdolsamad K. Amirkolaei; Marina M. Rubio Benito; Vikas Kumar; Nicholas Romano; Jeongwhui Hong; Brian C. Small (Animal Feed Science and Technology, 2025)

Effects of dietary arachidonic acid supplementation in low fishmeal and fish oil-free diets on growth performance, inflammatory response, gut histology, and non-specific immunity in sub-adult rainbow trout, Oncorhynchus mykiss - Jeongwhui Hong; Jose G. Ortiz; Wendy M. Sealey; Brian C. Small (Aquaculture, 2024)

Balancing dietary plant-based lipids and cholesterol to increase fillet omega-3 deposition in rainbow trout (Oncorhynchus mykiss) fed a diet without animal ingredients - Jeongwhui Hong; Jacob W. Bledsoe; Kenneth E. Overturf; Ronald W. Hardy; Brian C. Small (Aquaculture, 2024)

Utilization of functional feed additives to produce cost‐effective, ecofriendly aquafeeds high in plant‐based ingredients - Md. Sakhawat Hossain; Brian C. Small; Vikas Kumar; Ronald Hardy (Reviews in Aquaculture, 2024)
Fishmeals (FM) are the most superior protein sources in aquafeed. World‐wide growing demand and limited supply of FM limit its use as sole protein sources in aquafeed and force fish nutritionists to develop alternate protein‐based aquafeeds. However, increasing alternate proteins over a certain percentage reduces fish performance. Many attempts have been made (viz., manipulation of processing technology of feed ingredients and feed formulations, supplementation strategy) to overcome the negative effects of increasing alternative protein inclusion in aquafeeds. Among them, supplementation of functional feed additives (FuFAs) has received promising attention. Recently, several FuFA (nucleotides, organic acid, probiotics, prebiotics, and certain amino acids) have been administrated in alternative protein‐based aquafeeds and demonstrate increased efficiency of alternative protein utilization along with improved fish growth and health performances. However, numerous gaps remain in existing knowledge about the administration of exogenous FuFA in alternative protein‐based aquafeeds, including the effects on digestion, age/size‐related responses, species variations, absorption, metabolism, and influences on physiological responses. Application of biochemical and molecular technologies is important to better understand the underlying mechanisms of FuFA functions in alternate protein‐based aquafeed to improve fish and shrimp performance. Efforts are also needed by researchers and industrialists regarding production technologies to reduce functional feed supplement costs. Moreover, in‐depth research knowledge is needed considering the use of functional feeds to combat fish diseases and reduce dependence on antibiotics and chemical therapeutants, thereby making aquaculture more eco‐friendly.

Insect lipid in fish nutrition: Recent knowledge and future application in aquaculture - Md. Sakhawat Hossain; Brian C. Small; Ronald Hardy (Reviews in Aquaculture, 2023)
Insect lipid/oil is a by‐product of insect meal production. The quantity and nutritional quality of insect lipid varies with species, life stages, the kind of substrate used to raise the insects, as well as the extraction process. Insect lipid products have been successfully used in animal feeds as source of nutrients, notably energy and indispensable fatty acids. Further some insect lipid products are potential functional ingredients in feed formulations because of the existence of some functional compounds, for example, lauric acid and monolaurin in black solder fly larvae oil (BSFLO). To date, research on the effects of insect product inclusion in aquafeed mainly focused on insect meal as protein source rather than insect oil/lipid as a lipid source. Research to date indicates that insect lipids can replace traditional energy sources in fish nutrition without negatively affecting fish growth and feed utilization performance. By raising the amount of long‐chain polyunsaturated fatty acids in fish fillets, insect lipids can improve fillet quality. Insect lipids may also positively influence general health of fish by stimulating the immune system and manipulating the gut microbiota. As there is a crucial need for searching alternate lipid sources in aquafeed to extend limited global supplies of fish oil and due to the insect lipids content and its fatty acid quality, there is a pressing need to expand experimentation concerning their application in aquafeed to support sustainable growth of the aquaculture industry.

A geochemically informed leak detection (GILD) model for CO2 injection sites - Jiaan Wang; Wei Xiong; James B. Gardiner; Brandon C. McAdams; Brian W. Stewart; R. Burt Thomas; J. Alexandra Hakala; Christina L. Lopano; Mitchell J. Small (Applied Geochemistry, 2023)

Evaluation of a corn fermented protein with solubles (CFPS) as a complete soybean meal replacer in practical diets for Atlantic salmon (Salmo salar) - Md. Sakhawat Hossain; Yan Zhang; Brian C. Small (Aquaculture, 2023)

Effects of grid spacing on high-frequency precipitation variance in coupled high-resolution global ocean–atmosphere models - Charles X. Light; Brian K. Arbic; Paige E. Martin; Laurent Brodeau; J. Thomas Farrar; Stephen M. Griffies; Ben P. Kirtman; Lucas C. Laurindo; Dimitris Menemenlis; Andrea Molod; Arin D. Nelson; Ebenezer Nyadjro; et al. (Climate Dynamics, 2022)
High-frequency precipitation variance is calculated in 12 different free-running (non-data-assimilative) coupled high resolution atmosphere–ocean model simulations, an assimilative coupled atmosphere–ocean weather forecast model, and an assimilative reanalysis. The results are compared with results from satellite estimates of precipitation and rain gauge observations. An analysis of irregular sub-daily fluctuations, which was applied by Covey et al. (Geophys Res Lett 45:12514–12522, 2018. https://doi.org/10.1029/2018GL078926 ) to satellite products and low-resolution climate models, is applied here to rain gauges and higher-resolution models. In contrast to lower-resolution climate simulations, which Covey et al. (2018) found to be lacking with respect to variance in irregular sub-daily fluctuations, the highest-resolution simulations examined here display an irregular sub-daily fluctuation variance that lies closer to that found in satellite products. Most of the simulations used here cannot be analyzed via the Covey et al. (2018) technique, because they do not output precipitation at sub-daily intervals. Thus the remainder of the paper focuses on frequency power spectral density of precipitation and on cumulative distribution functions over time scales (2–100 days) that are still relatively “high-frequency” in the context of climate modeling. Refined atmospheric or oceanic model grid spacing is generally found to increase high-frequency precipitation variance in simulations, approaching the values derived from observations. Mesoscale-eddy-rich ocean simulations significantly increase precipitation variance only when the atmosphere grid spacing is sufficiently fine (< 0.5°). Despite the improvements noted above, all of the simulations examined here suffer from the “drizzle effect”, in which precipitation is not temporally intermittent to the extent found in observations.

A cohort study of personal and family history of skin cancer in relation to all-cause and cancer-specific mortality - James Small; Kristin Wallace; Elizabeth G. Hill; Bruce H. Thiers; Brian C. Leach; Anthony J. Alberg (Cancer Causes & Control, 2021)

A cohort study of personal and family history of skin cancer in relation to future risk of non-cutaneous malignancies - James Small; Kristin Wallace; Elizabeth G. Hill; Bruce H. Thiers; Brian C. Leach; Anthony J. Alberg (Cancer Causes & Control, 2019)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Spatial and temporal variability of herbaceous vegetation in an eastern deciduous forest - Christine J. Small; Brian C. McCarthy (Plant Ecology, 2003)